Wave Attractors on Enceladus - Van Oers, A.M. (author) (2016)
Enceladus, an enigmatic satellite. It orbits Saturn among many other moons, but the observations by Cassini of Enceladus were perhaps the most eagerly awaited. Enceladus did not disappoint: After Cassini's arrival in the Saturnian system interest has surged for this tiny moon. Many fascinating phenomena are taking place and Cassini has been observing these phenomena since 2005. From its rich and diverse surface, to its connection with Saturn's E-ring, to its high albedo; all are special phenomena. What makes Enceladus unique, however, is the region near its south pole. There, geysers spew material, including salts, from the interior of the satellite into space through openings in its icy crust. These openings or cracks are called ``tiger stripes'' and their orientation and position prove to be difficult to explain. The area near these tiger stripes is anomalously hot, with temperatures reaching far higher than anticipated. These high temperatures indicate heat is being transported from the interior to the surface, but this happens only near the south pole. The observed heating output is much larger than can be explained by current models for planetary heating. These observations make Enceladus and especially its south pole one of the most fascinating places in our Solar system. One special feature on Enceladus is its subsurface sea. Enceladus' subsurface sea is likely confined to the southern latitudes. Since the tiger stripes are located at the South pole and Enceladus' subsurface sea is likely confined to the region below the South pole, these two features seem linked. Did Enceladus' subsurface sea play a role in the formation of the tiger stripes? ince the field of ocean dynamics is very large, attention is restricted to one type of motion in the ocean: wave attractors. A wave attractor is an attractor for internal waves. These are waves that have their maximum displacement in the interior of a fluid. This is different from surface waves, which have their maximum displacement at the surface. These internal ...